Ultra-wideband for multiple access communications. - Qiu, Robert C. (IEEE Communications magazine)
Ultra-wideband wireless communications techniques have many merits, including an extremely simple radio that inherently leads to low-cost design, large processing gain for robust operations in the presence of narrowband interference, covert operations, and fine time resolution for accurate position sensing. However, there are a number of challenges in UWB receiver design, such as capturing multipath energy, intersymbol interference especially in a non-line-of-sight environment, and the need for high-sampling-rate analog-to-digital converters. In this article, we provide a comprehensive review of UWB multiple access and modulation schemes, and their comparison with narrowband radios. We also outline the issues with UWB signal reception and detection, and explore various suboptimal low-complexity receiving schemes.